Equilibrium curve of carbon dioxide adsorption–desorption using potassium carbonate on gamma-alumina in fluidized bed reactor. (November 2020) - Inmanee, Nithiwadee; Chaiwang, Pilaiwan; Chalermsinsuwan, Benjapon; Piumsomboon, Pornpote
Abstract: At present, global warming becomes a major problem affecting the world in many ways. The main cause is the releasing of large amounts of carbon dioxide (CO2 ) into the atmosphere. The reduction of CO2 is thus a tremendous challenge. The CO2 capture processes then are invented to account this problem. One of the essential basic information for designing and operating of these separation processes is the adsorption–desorption equilibrium. In this study, the equilibrium isotherms on potassium carbonate on gamma-alumina (K2 CO 3 ∕ γ -Al2 O3 ) solid sorbent were correlated with Langmuir, Freundlich, Sips and Toth models. The CO2 sorption capacities were measured with pressures at different system temperatures (45–90 °C). From the result, it was found that Sips isotherm was the suitable model (R 2 ranged between 0.91–0.99 with an error of less than 2.09%). When comparing the CO2 capture capacity with pure K2 CO3, the obtained CO2 capture capacities were improved by impregnating K2 CO 3 on the γ -Al2 O3 support.